Identification of Pests and Diseases on Begonia Plants (Begonia sp) in Sewu Kembang Tourism Village, Karanganyar - Adinda Mustika Kurnianingtyas; Inayah Romita Diani; Prayoga Felix Z (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Begonia (Begoniaceae) is one of the large genus in the Angiospermae group, with a distinctive leaf asymmetry. Begonias have considerable economic value and some Begonia plants have potential as medicinal plants and as vegetables. Pests and diseases are one of the problems in the development of Begonia cultivation. This study aims to identify and identify the types of pests and diseases that attack Begonia plants. The location of this research is in the area of ​​Sewu Kembang Tourism Park, Nglurah, Tawangmangu, Karanganyar Regency. This research was carried out from September 4 to October 3, 2021. This research was carried out for 30 days using 10 begonia plant samples. The tools used include a camera to take pictures and stationery to record data. The variables observed were pests and diseases that attack Begonia plants. In this study using direct observation and interviews with begonia plant owners. The data were analyzed by qualitative descriptive. The results of the study found 1 disease, namely nitrogen deficit and 2 pests, namely caterpillars and snails. Which causes damage to the leaves of the Begonia plant where the leaves of the Begonia plant are the attraction of the plant.